The Contributions of Holistic Children Ministry in Church Development in Emmanuel Burema Church of Uganda- Diocese of Kinkiizi - Owen Abaho (Uganda Christian University, 2025)
This research study was on holistic child ministry in Emmanuel Burema parish, kanyantorogo archdeaconry, kinkinzi Diocese. It presented five chapters which includes introduction, literature review, research methodology, data presentation and analysis, and discussion of the research findings and recommendation and conclusion. This research study hinges on problem statement, objectives of the study and research questions of the study. Data collected was analyzed on the basis of the latter and former. The data collected covered the current status, contributions and way forward for holistic child ministry in Burema parish, Kanyantorogo archdeaconry. The researcher used questionnaire, interview, and personal experience which he administered on different persons whom he arrived at using sampling techniques. Data collected was grouped and analyzed using tables, frequencies and percentages to come with the respondents and interviewees views on the research questions and objectives of the study. Therefore it was against these that the research findings in chapter four were discussed in chapter five and recommendations to address the holistic child ministry and finally conclusions made. The research findings showed that there was children ministry as evidenced by the activities such as children workshops, Sunday school though there was a gap for the implementation of holistic children ministry which contributes much to the development of the church. The church has however tried to put up some measures to address the challenges such as compassion international, Sunday school programs, reaching children with the gospel, and sensitizing parents about parenting. The researcher recommended some strategies that can help the church, government, parents, and church leaders to implement holistic child ministry for example developing curriculum for Sunday school, training children teachers, and parents acting as role models to children among others
Undergraduate Research